Mastering Ceph : infrastructure storage solutions with the latest Ceph release - Fisk, Nick (Packt Publishing, 2019)
Discover the unified, distributed storage system and improve the performance of applications Key Features Explore the latest features of Ceph's Mimic release Get to grips with advanced disaster and recovery practices for your storage Harness the power of Reliable Autonomic Distributed Object Store (RADOS) to help you optimize storage systems Book Description Ceph is an open source distributed storage system that is scalable to Exabyte deployments. This second edition of Mastering Ceph takes you a step closer to becoming an expert on Ceph. You'll get started by understanding the design goals and planning steps that should be undertaken to ensure successful deployments. In the next sections, you'll be guided through setting up and deploying the Ceph cluster with the help of orchestration tools. This will allow you to witness Ceph's scalability, erasure coding (data protective) mechanism, and automated data backup features on multiple servers. You'll then discover more about the key areas of Ceph including BlueStore, erasure coding and cache tiering with the help of examples. Next, you'll also learn some of the ways to export Ceph into non-native environments and understand some of the pitfalls that you may encounter. The book features a section on tuning that will take you through the process of optimizing both Ceph and its supporting infrastructure. You'll also learn to develop applications, which use Librados and distributed computations with shared object classes. Toward the concluding chapters, you'll learn to troubleshoot issues and handle various scenarios where Ceph is not likely to recover on its own. By the end of this book, you'll be able to master storage management with Ceph and generate solutions for managing your infrastructure. What you will learn Plan, design and deploy a Ceph cluster Get well-versed with different features and storage methods Carry out regular maintenance and daily operations with ease Tune Ceph for improved ROI and performance Recover Ceph from a range of issues Upgrade clusters to BlueStore Who this book is for If you are a storage professional, system administrator, or cloud engineer looking for guidance on building powerful storage solutions for your cloud and on-premise infrastructure, this book is for you.